Handling Evaluation Money Politic By Bawaslu Majalengka District In The 2019 Election - Herdiana, Deni; Dwiyandika, Dara (PT. Anagata Sembagi Education, 2024)
The purpose of this study is to determine and evaluate the handling of money politics by the Majalengka Regency Bawaslu. The research method used is descriptive qualitative with a data collection approach that involves direct interaction with key informants. The data sources in this study include the Head of Bawaslu, Bawaslu Commissioners, and Staff of the Violation Handling Division of Bawaslu Majalengka Regency. Data were collected through in-depth interviews and related documentation. This study found that the handling of money politics violations by the Majalengka Regency Bawaslu is still not optimal. Several factors affecting the effectiveness of handling are the limited number of Bawaslu members, which has an impact on limitations in patrolling and sweeping money politics activities. In addition, active community participation in reporting suspected cases of money politics is also still low, which hinders more effective detection and handling. This research identifies the need to increase the number of Bawaslu members as well as efforts to increase public awareness and participation in the reporting process, so that the handling of money politics cases can be carried out more thoroughly and efficiently.